Risk of Malignancy in Effusions according to the International System for Serous Fluid Cytopathology: A Review - Castilho Da Silva, Daniel José; Dos Santos, Caio Rodrigo; Xavier-Júnior, José Cândido Caldeira [UNESP] (Karger Publishers, 2024)
Introduction: The International Serous Fluid Cytopathology Reporting System (TIS) was developed to standardize communication among health professionals reporting analyses of serous fluid samples. The categories include non-diagnosis (ND), negative for malignancy (NFM), atypia of undetermined significance (AUS), suspected malignancy (SFM), and malignant (MAL). Each category was characterized by a risk of malignancy (ROM). Methods: We performed a literature review to analyze studies related to TIS using several sources, including PubMed, followed by a search of relevant cytopathology journal websites (American Cancer Society, Diagnostic Cytopathology, Journal of the American Society of Cytopathology, and Acta Cytologica and Cytopathology). The search included articles published between January 2020 and December 2023, using the terms international AND serous fluid system.Results: We identified 257 articles, of which 20 addressed the inclusion and exclusion criteria. The overall ROMs for each category were 23.55% for ND, 16.46% for NFM, 50.78% for AUS, 91.34% for SFM, and 98.21% for MAL. Conclusion: Considering the TIS-recommended ROM rates, the ND category was between the suggested intervals, while the SFM category rate was bigger than expected. The other categories (NFM, AUS, and MAL) were below expected values. SFM and MAL had a stronger association with MAL results. New studies are needed to determine each category's ROM rate from TIS accurately.
Keywords: Cytopathology; Effusions; Guidelines; International system; Pleural effusion